Pertanggung Jawaban Hukum Aparat Kepolisian atas Tindakan Salah Tangkap di Tinjau dari Kuhap dan Peraturan Polri No 14 Tahun 2011 tentang Kode Etik Profesi Polri - Husni Fahri Fani; Dini Dewi Heniarti (Bandung Conference Series: Law Studies, 2022)
Abstract. Wrong arrest or error in persona is an error against a suspect that occurs at the level of investigation and an error against a person that occurs at the level of prosecution and examination of justice. An error in persona is a dwaling, a misunderstanding or mistake on the part of the defendant against the person to be addressed. The definition of wrongful arrest or in-person error is not contained in the Criminal Procedure Code or other laws and regulations. The error can occur at the time of an arrest, or detention, or prosecution, or during an examination by a judge in court until the case is decided. This understanding is implied in Article 95 of the Criminal Procedure Code which discusses compensation for people who are arrested, detained, prosecuted and tried without any reason based on law or mistakes regarding the person. This research method uses a normative juridical approach, this research is descriptive analytical, the type of research carried out by the author is qualitative research, and emphasizes the process and meaning contained in the phenomenon. The implementation of the investigation process at the Sukabumi Police has not been said to have complied with the predetermined procedure, because in its application there are still interrogations or asking for information from the suspect by making the suspect feel afraid and not free to provide information. In the Criminal Procedure Code which adheres to the accusator principle, where the suspect is seen as a subject who has the right to give information freely in submitting a defense to the investigator or judge and the testimony of the suspect or witness to the investigator is given without pressure from anyone or in any form. Abstrak. Salah tangkap atau eror in persona adalah kekeliruan terhadap tersangka yang terjadi pada tingkat pemeriksaan penyidikan maupun kekeliruan terhadap orangnya yang terjadi pada tingkat penuntutan dan pemeriksaan keadilan. Eror in persona adalah suatu dwaling, suatu salah paham atau kekeliruan dari pihak terdakwa terhadap orang yang akan dituju. Pengertian mengenai salah tangkap atau eror in persona tidak terdapat dalam KUHAP maupun peraturan perundang-undangan lainnya. Kekeliruan itu bisa terjadi pada saat dilakukan penangkapan, atau penahanan, atau penuntutan, atau pada saat pemeriksaan oleh hakim di pengadilan sampai perkaranya diputus. Pengertian ini tersirat dalam Pasal 95 KUHAP yang membahas tentang ganti rugi terhadap orang yang ditangkap, ditahan, dituntut dan diadili tanpa alasan yang berdasarkan undang-undang atau kekeliruan mengenai orangnya. Metode Penelitian ini menggunakan metode pendekatan yuridis normatif, penelitian ini bersifat deskriptif analitis, jenis penelitian yang dilakukan oleh penulis adalah penelitian kualitatif, serta menonjolkan proses dan makna yang terdapat dalam fenomena tersebut. Pelaksanaan proses penyidikan di Polres Sukabumi belum bisa dibilang sudah sesuai dengan prosedur yang telah ditentukan, karena dalam penerapanya masih terdapat introgasi atau meminta keterangan tersangka dengan cara membuat tersangka merasa takut dan tidak leluasa memberikan keterangan. Dalam KUHAP yang menganut asas akusator, dimana tersangka dipandang sebagai subjek yang berhak memberikan keterangan secara bebas dalam mengajukan pembelaan kepada penyidik atau hakim dan keterangan tersangka atau saksi kepada penyidik diberikan tanpa tekanan dari siapa pun atau dalam bentuk apapun.